TRADISI TINGKEBANG DI BAKALANRAYUNG JOMBANG - Yunia Rohimatin (Qurthuba: The Journal of History and Islamic Civilization, 2023)
Abstract: This thesis is entitled “Acculturation of the Tingkeban Tradition (Case Study in Bakalanrayung Village, Kudu District, Jombang Regency)”. This study has two research focuses, namely the implementation of the Tingkeban ceremony in Bakalanrayung Village, Kudu District, Jombang Regency, and the cultural elements that are acculturated in the Tingkeban ceremony in Bakalanrayung Village. This study uses the historical research method according to Kuntowijoyo, with several stages: topic selection, heuristics, verification, interpretation, and historiography. The anthropological approach is used to analyze the cultural studies of the Tingkeban tradition through various cultural elements as descriptive objects of culture. The theory used is the theory of acculturation and the theory of religion from Koentjaraningrat. The results of this study are (1) the stages of implementing Tingkeban starting with determining the time and place, followed by preparing the items needed, preparation before the event, and then carrying out the main event procession consisting of khataman, taking cengkir by the father-to-be, recitation, watering and holy, changing cloth or jarik, and selling dawet. (2) There are various cultural elements that blend with each other. These cultural elements consist of Animism and Dynamism beliefs, Hindu culture, and elements of Islamic culture. Keywords: acculturation, Bakalanrayung, tingkeban